Synthesis, Spectroscopic and Biological Characterization of the Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) Complexes with a New Macrocylic Tridentate [ONO] Ligand - Bootwala, Sakina; Aruna, K. (Asian Journal of Chemistry, 2012)
Complexes of general formula [ML2] where M = manganese(II), cobalt(II), nickel(II), copper(II) and zinc(II), L = ethyl 2-{[(1E,2E)-2-(hydroxyimino)-1-phenyl ethylidene]amino}-4,5,6,7- tetrahydro-1-benzothiophene-3-carboxylate have been prepared. All the complexes were characterized by analytical analysis and physico-chemical methods. The ligand behaves as a tridentate chelating agent and bonded to the metal ion through azomethine nitrogen, ester carbonyl and oximino oxygen atom. Electronic spectra and magnetic susceptibility measurement reveal octahedral geometry. The complexes are found to be non-electrolytic in nature on the basis of low molar conductance. The metal complexes have been screened for their antibacterial activity.